Macromolecular organic matter in samples of the asteroid (162173) Ryugu - Yabuta, Hikaru; Cody, George D; Engrand, Cécile; Kebukawa, Yoko; De Gregorio, Bradley; Bonal, Lydie; Remusat, Laurent; Stroud, Rhonda; Quirico, Eric; Nittler, Larry; Hashiguchi, Minako; Komatsu, Mutsumi; et al. (Science (American Association for the Advancement of Science), 2023)
Samples of the carbonaceous asteroid (162173) Ryugu were collected and brought to Earth by the Hayabusa2 spacecraft. We investigated the macromolecular organic matter in Ryugu samples and found that it contains aromatic and aliphatic carbon, ketone, and carboxyl functional groups. The spectroscopic features of the organic matter are consistent with those in chemically primitive carbonaceous chondrite meteorites that experienced parent-body aqueous alteration (reactions with liquid water). The morphology of the organic carbon includes nanoglobules and diffuse carbon associated with phyllosilicate and carbonate minerals. Deuterium and/or nitrogen-15 enrichments indicate that the organic matter formed in a cold molecular cloud or the presolar nebula. The diversity of the organic matter indicates variable levels of aqueous alteration on Ryugu's parent body.